Study of Factors to Increase the Usage Rate of Generic Drugs in Platelet Aggregation Inhibitors - Takaaki Suzuki BS; Mari Iwata BS; Mika Maezawa MS; Kiyoka Matsumoto BS; Mizuki Tanaka BS; Riko Satake BS; Misaki Inoue BS; Yu Yoshida BS; Kazuhiro Iguchi PhD; Mitsuhiro Nakamura PhD (SAGE Publishing, 2023)
To reduce pharmacy-related medical expenses, it is necessary to reduce drug costs. One way to achieve this is by increasing the usage rate of generic drugs. The purpose of this study was to identify platelet aggregation inhibitors (PAIs) that contribute to high drug costs and are sold as brand-name drugs in order to increase the usage rate of generic drugs, and to analyze the factors that affect the usage rate of generic drug. We conducted a cross-sectional study based on the National Database of Health Insurance Claims and Specific Health Checkups of Japan Open Data Japan (NODJ) of the Ministry of Health, Labor and Welfare and datasets containing related medical information from official statistical surveys such as the Basic Survey on Wage Structure. Monthly personal income in each prefecture were negatively correlated with outpatient out-of-hospital and outpatient in-hospital prescriptions of the PAIs clopidogrel (75 mg), cilostazol (50 mg), cilostazol (100 mg), and ticlopidine (100 mg), but not between monthly personal income and outpatient out-of-hospital prescription of ticlopidine (100 mg). For outpatient out-of-hospital prescriptions and outpatient in-hospital prescriptions, negative correlation was generally observed between the usage rate of generic drug and monthly personal income, except for ticlopidine (100 mg), which has the lowest price among the brand-name drugs. The usage rate of generic PAIs is negatively correlated with monthly personal income. Promoting the use of generic drugs among high-income earners might be necessary to further increase the usage rate of generic drug.